SOSIALISASI ALAT KESELAMATAN DAN MENGHINDARI FAKTOR PENYEBAB KECELAKAAN PERAHU NELAYAN DESA PANTAUAN - puji amalia; Rusman Rusman; Zainal Abidin; Mika Patayang (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The purpose of this program is to facilitate the group of fishermen with the safety equipment and give the information about the importance of Occupational Health and Safety (OHS). It was conducted in Pantuan Village, Kutai Kartanegara, on 08 & 09 July 2021. This activity is carried out directly by implementing a very strict Health protocol due to pandemic. Based on these activities, it can be concluded that the implementation was successfully carried out with some indicators, such as the number of participants, the objectives of the activity, and their understanding with the material. The follow-up to this program is to maintain communication with the head of the fishermen to monitor the use of the safety equipment that has been provided. Keywords: safety, safety equipment, fisherman